Enhancement of TiO2 Photocatalyst Using Rare Earth Oxide (La2O3) via a Simple Preparation Method for Degradation of Methylene Blue under Visible Light - Natsir, Taufik Abdillah; Pamungkas, Alam Reformasi Putra; Aprilita, Nurul Hidayat (Universitas Jenderal Soedirman, 2024)
The modification of TiO2 using rare earth oxide (La2O3) to increase the photodegradation activity of TiO2 under visible light has been conducted. The goal of this research is to identify the influence of La2O3 on the TiO2 to the photocatalytic activity of TiO2. The mixed oxide of TiO2/La2O3 was prepared using the precipitation method. The as-prepared catalyst was then calcined at 923 K. The photocatalyst was characterized using SRUV, XRD, FTIR, and SEM-EDX. The results showed that the photocatalyst activity of TiO2/La2O3-923 under visible light in the degradation of methylene blue was higher than pristine TiO2. The decrease in bandgap energy of TiO2/La2O3-923 from 3.2 eV to 3.01 eV was not the main factor in the increase of photocatalytic activity of TiO2/La2O3-923. The optimum condition of photodegradation of MB was obtained when the ratio of TiO2/La2O3 was 5, the concentration of MB was 10 ppm, the reaction time was 300 min, and the mass of the photocatalyst was 0.25 g. The reusability of TiO2/La2O3-923 was stable up to 3 sequent runs with the MB photodegradation of more than 90%. The mechanistic study of the mixed oxide TiO2/La2O3 showed that the hydroxyl radical played an important role in its high photocatalytic. Keywords: TiO2-La2O3, photocatalyst, visible light, methylene blue